(3ETcGdGJ GdJfajP aj CMcGe GdbVGA GdEOGQj (B/s - (3HSjhfj, YHO GdQDha gGTes ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdacQ GdLGeYj,s, 2017)
(3Ydi GdQZe ef GJLGg GdHGMKjf aj abg GdbGfhf GdEOGQj UhH OQGSI GdELQGAGJ hGdeQGaYGJ GdEOGQjI, EdG Ef gPG GdGJLGg de jhd GgJeGeg efGRYGJ GdJfajP ShGA GdehVhYjI efgG Ch GdhbJjI (B((3GdETcGdGJ(B)(3, eY Cf gPg GdefGRYGJ JKjQ GdcKjQ ef GdeTcdGJ GdJj jfHZi EjLGO Mdhd dgG, hPdc dJaGOi JfGRY GdGNJUGU Hjf GdbVGA GdYGOj hGdbVGA GdEOGQj(B. (3hERGA YRha Gdabg Yf OQGSI efGRYGJ GdJfajP aj GdbGfhf GdEOGQj, abO GfHQi GdbGVj GdEOGQj dJCUjd gPg GdefGRYGJ hhVY GdMdhd GdYedjI dgG eeG jcTa Yf GHJOGY hGHJcGQ gPG GdbGVj hOhQg GdNdGb aj eLGd fXQjGJ GdbGfhf GdEOGQj(B. (3hdeG cGf HMKfG GdeGKd df jJfGhd HGdOQGSI cd efGRYGJ GdJfajP, hEfeG SjbJUQ abW Ydi ehVhY hGMO efgG hgh GdNGU HefGRYGJ GdJfajP GdhbJjI (B((3ETcdGJ GdJfajP(B)(3, hdeG cGf bGfhf eLdS GdOhdI GdeUQi de jJfGhd aj fUhUg gPg GdefGRYGJ, GdCeQ GdPj OaY GdbGVj GdEOGQj Edi Cf jSJQTO HfUhU bGfhf GdeQGaYGJ hjWHbgG Ydi efGRYGJ GdJfajP GdhbJjI HeG dG jJYGQV eY WHjYI GdefGRYI GdEOGQjI hQhGHW GdbGfhf GdYGe(B.s
(3HHdjhLQGajI (B: (3UaMI (B101-105.s
Keywords: (3GdbVGA GdEOGQjs -- (3eUQs; (3JfajP GdCMcGes -- (3eUQs